Two new species of the Anemadus taiwanus species-group (Coleoptera: Leiodidae: Cholevinae: Anemadini) from China - Wang, Cheng-Bin (Zootaxa, 2016)
Anemadus perreaui sp. nov. and A. sichuanus sp. nov., both belong to the A. taiwanus species-group (Coleoptera: Leiodidae: Cholevinae, Anemadini), are described from Sichuan Province, China. Color plates and line drawings are offered to illustrate their important characteristics. A key to all species of the group is compiled so as to include the two new species.